THE INFLUENCE OF RETURN ON EQUITY, CURRENT RATIO AND EARNING PER SHARE TOWARD STOCK PRICE OF CONSUMER GOODS INDUSTRY LISTED ON THE INDONESIA STOCK EXCHANGE - Melina, Melina; Steffani, Steffani (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2022)
The aim of this research is to find out the influence of return on equity, current ratio, and earnings per share on the stock price of consumer goods industry listed on the Indonesia Stock Exchange (IDX) for the year 2017-2020. This is quantitative research with a purposive sampling method as the selected sampling method to be used. The data is secondary data derived from Indonesia Stock Exchange. In total, companies that meet the sample criteria amount to 25 companies from 2017 to 2020, resulting in a total of 100 data. The data analysis method applied is multiple linear regression which is processed through SPSS 25. The findings of this research show that, partially, return on equity has an insignificant influence toward stock price, whereas current ratio and earnings per share have a significant influence toward stock price of consumer goods industry listed on the Indonesia Stock Exchange (IDX) for the year 2017-2020. On the other hand, those three independent variables simultaneously have significant influence on stock price.